Layanan Purna Jual dan Perlindungan Hukum Bagi Konsumen - Fransiska Novita Eleanora; Diana Fitriana (KRTHA BHAYANGKARA, 2023)
A consumer is anyone who uses goods and/or services available in society for the benefit of himself, also his family and other people and even other living creatures and not for trading, and this is also for buying and selling transactions both directly and face to face. Consumers are also entitled to protection through rules governing rights and obligations in realizing legal protection, and more emphasis on consumer rights where there are several rights to be protected, namely the right to choose, the right to obtain information, the right to security and also the right to heard. These consumer rights relate to after-sales service if the consumer in purchasing goods and/or services is carried out in follow-up consultation between the buyer and the consumer or there is a warranty period such as replacement of damaged goods, as well as maintenance and provision of spare parts, but with a certain period of time. from the warranty period made by business actors because there are certain products whose warranty period is not as stated or promised and of course provides consumer limitations and the rights of consumers cannot be fully realized or fulfilled.